Monogamy or monogamish? Re-examining monogamy in Peromyscus californicus - Meléndez-Rosa, Jesyka; Lacey, Eileen A. (THERYA, 2022)
California mice have been widely recognized as one of the few examples of ‘true’ genetic monogamy in mammals and are one of only four mammalian species considered to be both genetically and socially monogamous. The mating system of this species, first described by David O. Ribble (1991), was initially investigated in a single population by integrating both behavioral data and DNA fingerprinting to classify P. californicus as monogamous. Here, we investigated the parentage of field sampled litters of California mice across 4 populations using both classic field methods and modern microsatellite analyses. We putatively identified male-female mouse pairs in the field using capture localities and transfer of fluorescent pigment between individuals. We then used microsatellite loci to genotype pregnant adult females, their embryos, and the adult males identified in the field as the partners of those females. We identified occurrences of extra-pair paternity in 3 out of the 4 populations of California mice, calling in to question the designation of this species as genetically monogamous (Figure 1 and Table 1). We suggest a careful re-examination of the mating system of this species using modern molecular methods to analyze a greater number of samples representing multiple sampling localities. Future studies of this species should prove particularly informative regarding the correlates of extra-pair mating and, hence, the adaptive bases for the maintenance of male-female pair bonds in the absence of true genetic monogamy.